Bi‐allelic VPS16 variants limit HOPS/CORVET levels and cause a mucopolysaccharidosis‐like disease. Issue 5 (3rd May 2021) - Sofou, Kalliopi; Meier, Kolja; Sanderson, Leslie E; Kaminski, Debora; Montoliu‐Gaya, Laia; Samuelsson, Emma; Blomqvist, Maria; Agholme, Lotta; Gärtner, Jutta; Mühlhausen, Chris; Darin, Niklas; Barakat, Tahsin Stefan; et al.
Abstract: Lysosomal storage diseases, including mucopolysaccharidoses, result from genetic defects that impair lysosomal catabolism. Here, we describe two patients from two independent families presenting with progressive psychomotor regression, delayed myelination, brain atrophy, neutropenia, skeletal abnormalities, and mucopolysaccharidosis‐like dysmorphic features. Both patients were homozygous for the same intronic variant in VPS16, a gene encoding a subunit of the HOPS and CORVET complexes. The variant impaired normal mRNA splicing and led to an ~85% reduction in VPS16 protein levels in patient‐derived fibroblasts. Levels of other HOPS/CORVET subunits, including VPS33A, were similarly reduced, but restored upon re‐expression of VPS16. Patient‐derived fibroblasts showed defects in the uptake and endosomal trafficking of transferrin as well as accumulation of autophagosomes and lysosomal compartments. Re‐expression of VPS16 rescued the cellular phenotypes. Zebrafish with disrupted vps16 expression showed impaired development, reduced myelination, and a similar accumulation of lysosomes and autophagosomes in the brain, particularly in glia cells. This disorder resembles previously reported patients with mutations in VPS33A, thus expanding the family of mucopolysaccharidosis‐like diseases that result from mutations in HOPS/CORVET subunits. Synopsis: This study describes two cases of developmental regression with features resembling mucopolysaccharidosis‐like disease, caused by a recessive intronic variant in the HOPS/CORVET subunit VPS16. The cellular consequences of the mutation are characterized in patient‐derived cells and a zebrafish model. Patients show delayed myelination, brain atrophy, neutropenia, skeletal abnormalities and mucopolysaccharidosis‐like dysmorphic features. The reduced levels of VPS16 in patient‐derived fibroblasts cause decreased levels of HOPS/CORVET complexes, impaired transferrin endocytosis and accumulation of degradative compartments, phenotypes that are rescued upon re‐expression of VPS16. A zebrafish model recapitulates patient phenotypes by also showing delayed myelination and accumulation of degradative compartments. Abstract : This study describes two cases of developmental regression with features resembling mucopolysaccharidosis‐like disease, caused by a recessive intronic variant in the HOPS/CORVET subunit VPS16. The cellular consequences of the mutation are characterized in patient‐derived cells and a zebrafish model.